Trophy hunting is not one big thing - Hare, D (Springer, 2023)
Few topics in wildlife conservation are as controversial, emotive, or command as much public and political attention, as trophy hunting. International discourses regarding trophy hunting are characterised by radically contradictory assertions, ranging from claims that trophy hunting is a humane and socially acceptable wildlife management tool which benefits more animals than it kills, to claims that it is cruel, socially unacceptable, and drives species to extinction. So, which is it? We argue that using a single, blanket term “trophy hunting” obscures substantial and important variation in how and why people pay to hunt and keep trophies. Consequently, polarised disagreements over whether “trophy hunting” is good or bad, acceptable or unacceptable, beneficial or harmful, conflate arguments about fundamentally different activities. We urge conservation scientists and practitioners, politicians, journalists, and advocates on all sides to communicate more clearly and carefully about which specific hunting activities they believe are right or wrong, beneficial, or harmful, acceptable or unacceptable, to whom, and for what reasons.